Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.5812/archcid.62955
|View full text |Cite
|
Sign up to set email alerts
|

Functional Cytotoxin Associated Gene A in Helicobacter pylori Strains and Its Association with Integrity of Cag-pathogenicity Island and Histopathological Changes of Gastric Tissue

Abstract: Objectives: Existence of cytotoxin associated gene A (cagA) is considered as a marker for detection of an oncogenic Helicobacter pylori strain. Expression of cagA in the strains with incomplete delivery system (partial CagPAI) could convert them to less virulent strains.This study was aimed to analyze expression of cagA in H. pylori strains presenting diverse cagPAI and its effect on histopathological changes of the gastric tissue. Methods: Clinical strains of H. pylori and related histopathological data were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
1
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 59 publications
2
1
0
2
Order By: Relevance
“…Notably, the 26695 strain promoted significantly more IL-8 than did the GD13 strain. Our data are consistent with those of previous studies showing that CagA is a determining factor in the induction of IL-8 release and that CagA induces IL-8 in fibroblasts via a pathway similar to that in AGS cells 21,22 . Our data also showed that NHEJmediated repair of DSBs decreased in cells infected with the 26695 strain but remained at a similar level in cells infected with the GD13 strain.…”
Section: Discussionsupporting
confidence: 93%
“…Notably, the 26695 strain promoted significantly more IL-8 than did the GD13 strain. Our data are consistent with those of previous studies showing that CagA is a determining factor in the induction of IL-8 release and that CagA induces IL-8 in fibroblasts via a pathway similar to that in AGS cells 21,22 . Our data also showed that NHEJmediated repair of DSBs decreased in cells infected with the 26695 strain but remained at a similar level in cells infected with the GD13 strain.…”
Section: Discussionsupporting
confidence: 93%
“…The majority of the strains in our study showed partially deleted cagPAI genotype (61.9%), a similar to those of previous studies (Ahmadzadeh et al 2015;Alfizah et al 2013;Hanafiah et al 2020). As explained in a previous study (Hanafiah et al 2020), the lack of intactness in the cagPAI within these strains was due to different gene detection method having been used in the other study (Fazeli et al 2017). As in other studies, cagPAI might not be conserved as deletions within islands can occur, and socio-demographic and geographical factors also play essential roles in the variation of cagPAI diversity in H. pylori (Olbermann et al 2010;Ta et al 2012).…”
Section: 'Hummingbird' Phenotype Formationsupporting
confidence: 90%
“…H. pylori strain 26695, a human gastric pathogen, was used as a positive control in this study (Ashktorab et al, 2008;Fazeli et al, 2016). H. pylori strain 26695 was cultured on HBA plates at 37 o C under microaerobic conditions generated using CampyGen 2.5L Atmosphere Generation System (Thermo Fisher Scientific) for 48 h before being used in experiments.…”
Section: Bacterial Strains Used In This Studymentioning
confidence: 99%